Tren dan Arah Penelitian Global tentang Local Wisdom dan Sustainable Chemistry Education: Analisis Bibliometrik 2014–2024 (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to map global research trends and directions concerning the integration of local wisdom and sustainable chemistry education from 2014 to 2024 using bibliometric analysis. Data were collected through Publish or Perish (PoP) from Google Scholar using the keywords (“local wisdom” AND “chemistry education” AND “sustainability” AND “bibliometric analysis”). A total of 996 documents were retrieved, and after screening based on the PRISMA 2020 guidelines, 230 articles were analyzed using VOSviewer and Bibliometrix (R). The results reveal that publications related to local wisdom and sustainable chemistry education experienced a fluctuating trend, peaking in 2020 and declining in subsequent years. The co-occurrence mapping identified three main clusters indigenous knowledge, local wisdom, and ethnoscience that are interconnected in forming a conceptual framework for culturally rooted and sustainability-oriented chemistry education. These findings emphasize the importance of integrating local cultural values with green chemistry principles and the Education for Sustainable Development (ESD 2030) agenda to enhance students’ scientific literacy and ecological awareness. This research provides a theoretical and empirical basis for developing chemistry curricula and educational policies that are responsive to socio-cultural contexts and global sustainability challenges.